2019
DOI: 10.3892/mmr.2019.10197
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‑199a‑5p attenuates hypoxia/reoxygenation‑induced cytotoxicity in cardiomyocytes by targeting the HIF‑1α‑GSK3β‑mPTP axis

Abstract: MicroRNAs (miRs) have been identified as critical regulatory molecules in myocardial ischemia/reperfusion injury; however, the exact expression profile of miR-199a-5p in reperfusion injury and the underlying pathogenic mechanisms remain unclear. In the present study, it was revealed that miR-199a-5p expression was significantly increased in the plasma of patients with acute myocardial infarction and in a H9c2 cell model of oxygen-glucose deprivation and reperfusion (OGD/R) via reverse transcription-quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…Cardiac adverse hypertrophy remains the major risk factor for heart failure, which represents one of the leading causes of re-hospitalization and death in general population 17 , 19 . In this context, cardiomyocyte necrosis and mechanical stretching cause the release of circulating soluble sST2 isoform 8 , 20 , 21 , a key biomarker used to diagnose cardiac disease conditions accurately and to effectively prognosticate the high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac adverse hypertrophy remains the major risk factor for heart failure, which represents one of the leading causes of re-hospitalization and death in general population 17 , 19 . In this context, cardiomyocyte necrosis and mechanical stretching cause the release of circulating soluble sST2 isoform 8 , 20 , 21 , a key biomarker used to diagnose cardiac disease conditions accurately and to effectively prognosticate the high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this up-regulation increases apoptosis 15 and inhibits cell proliferation 16 . Pharmacological inhibition of miR-199-5p attenuates hypoxia/reoxygenation-induced cytotoxicity and decreases phenylephrine-induced cardiomyocyte hypertrophy 17 , 18 , indicating that the inhibition of this miRNA might serve as a novel therapeutic approach for treating HF. Studies specifically designed to assess the potential role and mechanism of miR-199a in the treatment of HF are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the aforementioned considerations, rising attempts were made to evaluate whether roxadustat or other related compounds could produce any modifications on various types of ionic currents (e.g., delayed-rectifier K + current [ I K (DR ) ], erg -mediated K + current [ I K(erg) ], and voltage-gated Na + current [ I Na ]) in pituitary tumor (GH 3 ) cells. Moreover, earlier numerous studies have reported the effective regulations of HIF-1α expression present in heart-derived H9c2 myoblasts [24,28,29,30,31,32,33,34,35]. Thus, we further decided to investigate the possible actions of roxadustat on I K(DR) in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2) also revealed that miR-103a-3p serves a protective role in myocardial I/R injury. Liu et al (28) demonstrated that miR-199a-5p expression affects hypoxia/reoxygenation-induced cytotoxicity in cardiomyocytes. Additionally, Peng et al (20) demonstrated that miR-133, miR-1291 and miR-663b expression was significantly increased in AMI compared with controls.…”
Section: Discussionmentioning
confidence: 99%